Layered intercalation compounds: Mechanisms, new methodologies, and advanced applications. (April 2020) - Laipan, Minwang; Xiang, Lichen; Yu, Jingfang; Martin, Benjamin R.; Zhu, Runliang; Zhu, Jianxi; He, Hongping; Clearfield, Abraham; Sun, Luyi
Abstract: The structural characteristics of two-dimensional (2-D) materials result in unique physical, electronic, chemical, and optical properties, making them potentially useful in a wide range of applications. These unique properties can be fine-tuned and enhanced via intercalation, expanding the applications of various 2-D intercalation compounds to a much wider scope. This article aims to provide an overview of innovations in the field of intercalation chemistry of 2-D intercalation materials, as well as to highlight their leading applications. A brief perspective on the intercalation of 2-D layered compounds is provided, focusing on mechanisms, approaches, and influential factors involving intercalation. Insights into the potential applications, challenges, and future opportunities of 2-D intercalated materials are discussed.